2005
DOI: 10.2133/dmpk.20.415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bayesian Predictability of Vancomycin Concentration Using Population Pharmacokinetic Parameters in Pediatric Patients

Abstract: The objective of this study was to evaluate the Bayesian predictability of vancomycin (VCM) pharmacokinetics in Japanese pediatric patients using one-compartment population pharmacokinetic (PPK) parameters, which we reported previously. The validity of the PPK model was evaluated by bootstrap method and cross validation method, and the Bayesian predictive performance was examined. The predictive performance of the PPK model for premature patients was also examined. The cross validation method showed the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The observed relationship between serum clearance of vancomycin and postmenstrual age agree with the fact that vancomycin is cleared renally by glomerular filtration and that there is a positive relationship between postmenstrual age and maturation of renal function [17–19].…”
Section: Discussionsupporting
confidence: 82%
“…The observed relationship between serum clearance of vancomycin and postmenstrual age agree with the fact that vancomycin is cleared renally by glomerular filtration and that there is a positive relationship between postmenstrual age and maturation of renal function [17–19].…”
Section: Discussionsupporting
confidence: 82%
“…Because kinetic disposition is quite different between adult patients and pediatric patients due to differences in body size, fluid compartments and drug elimination by urinary excretion or drug metabolism (Onishi et al, 2005), these data may agree with the previous studies.…”
Section: Therapeutic Drug Monitoringsupporting
confidence: 89%
“…According to these results, Bayesian predictability seems generally acceptable. The accuracy of Bayesian estimation depends on sampling times, [24][25][26] and it is reported that the estimation error for distribution volume is large but that for clearance is relatively small in case using only trough data.…”
Section: Comparison Of Patients' Characteristicsmentioning
confidence: 99%